Signalling legitimacy for SMEs transition environments: The case of the Bulgarian IT sector - Olga Ivanova; Sylvaine Castellano (Journal for East European Management Studies, 2012)
This research looks at legitimacy challenges of SMEs evolving in transition environments. Facing lower visibility, higher institutional pressures and limited resources, SMEs experience stronger need to demonstrate their legitimacy, their adherence to the requirements of evaluating audiences. Two types of legitimacy are discussed - functional and relational - that better capture the legitimacy needs of SMEs in transitional contexts. Being multi-dimensional constructs, their dimensions are identified, and measurements are proposed and tested using the structural equation modelling technique. The model was tested on data from the Bulgarian IT sector. – – Diese Untersuchung befasst sich mit den Herausforderungen der Legitimation von KMU in sich stark verändernden Umwelten. Angesichts geringerer Sichtbarkeit, höherer institutioneller Zwänge und begrenzter Ressourcen haben KMU eine stärkere Notwendigkeit, ihre Legitimität, ihre Befolgung von Anforderungen eines kritischen Publikums zu demonstrieren. Zwei Arten von Legitimität werden diskutiert - die funktionale und die relationale - das dem besseren Erfassen der Legitimitätsbedürfnisse von KMU in Übergangssituationen dient. Ihre Dimensionen werden identifiziert sowie Messungen vorgeschlagen und getestet, mit Hilfe der Strukturgleichungsmodell-Technik. Das Modell wurde basierend auf Daten aus der bulgarischen IT-Branche getestet.
Keywords: 650; signalling theory; organisational legitimacy; transition environments; SMEs